(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
An hepta (pyridinium) bis (hexachlorobismuthate (III)) nitrate, (C5H6N)7(BiCl6)2(NO3) crystallizes at room temperature in the monoclinic system, space group P21/n, with the following unit-cell parameters: a = 9.555(1) Å, b = 16.847(1) Å, c = 32.522(1) Å, β = 94.37° , V = 5219.8 Å3 and four molecules per unit cell. Its crystal structure was determined and refined down to R1 = 0.0504, wR2 = 0.0667. The structure of the title compound, (C5H6N)7(BiCl6)2(NO3) consists of seven monoprotonated pyridinium (C5H6N)+ cations, two independent octahedron [BiCl6]3- and an isolated NO3- anion. These entities are linked together through N-H.....Cl and N-H.....O hydrogen bonds, originating from the (C5H6N)+ groups and the isolated anion of nitrate to forming a three dimensional network.